Le logement social et l’espace intermédiaire extérieur : proposition d’un contrat social - Messaoud ABBAOUI; Boubakeur GUESSAS (Cinq Continents, 2018)
Social housing and external intermediate space: proposal for a social contract. Social housing is intended, according to the law in Algeria, for the citizen who is not able to pay an expensive rent or to buy housing. It is financed today by new resources mobilized within the framework of the FONAL (Funds National of Housing) supplied with social works funds like social treasury cases and mutual insurance companies. Its external intermediate space (access of housing, alley, passage, playground…) is often adapted in an illegal way without any consideration. Case examples are studied in the 200, 444 and 500 housing units of Setif’s town. In order to avoid illegal appropriations and to enhance the external intermediate space, it is necessary that inhabitants as well as State services: Real Estate Promotion and Management Office (OPGI), National Housing Fund (FONAL), Communal People's Assembly (Municipality) and Social Office of Proximity organ placed under the authority of the wali (prefect) conclude between them a pact, a social contract. This paper propose a social contract with clauses that inhabitants and State services must respect for the good external intermediate space performance and its appropriation in a legal way.